Strategi Pemulihan Pasar Badung Sebagai Daya Tarik Wisata Di Kota Denpasar - Ni Made Mei Widiari; I Nyoman Sunarta (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2017)
This research is done in one of the largest traditional market in Denpasar, namely is Badung Market. Badung Market located on Gajah Mada street, its about 1 Km to the West of the Catur Muka Statue, in Denpasar Downtown. This research aims to determine how the recovery strategy tourism of Badung Market as a tourist attractions. This research was analyzed by the concept of a tourist attraction, and also using the concept of markets and traditional markets. After that, this research using the qualitative research of methodologies. This data was obtained from interviews of market management and direct observations in Badung Market. The damage that occurred in Badung Market that will do by recovery strategy. This aims to rebuild market buildings that was broke. This process requires several stage, namely are: physical intervention, rehabilitation of economic and social/institusional revitalotations. Post-fire made the biggest market in Denpasar this being lost daily activities. While this relokalisasiBadung market is still running. The damages that occur in the Badung Market will now do the recovery strategy, aims to rebuild the market buildings that have been damaged. Keyword: market, the recovery strategy, tourist attractions.